PENGARUH FORMALIN, DIAZEPAM DAN MINUMAN BERALKOHOL TERHADAP KONSUMSI PAKAN, MINUM DAN BOBOT TUBUH Mus musculus - Saraswati, Tyas Rini; Indraswari, Endah; Nurani, Nurani (JURNAL SAINS DAN MATEMATIKA, 2009)
ABSTRACT—Diazepam, formalin and drink which contain alcohol are substances that can be a toxic if they are accumulated in a body. Drink that contains alcohol can make someone drunk. Diazepam is a medicine that calms and its function is to decrease neuron activity. While formalin which is to used as food preservation causes metabolism disorder. This aim of this research was to investigate and analyze the physiological aspect of M musculus body after it was treated with diazepam, formalin and drink alcoholic. The research used completely Randomize Design. The animal that was in experiment were 16 male M musculus and divided into 4 treatments and 4 replications. The treatments were P0 (Control), P1 (0.04 mg Diazepam), P2 (100 ppm Formalin), P3 (Drink which contains 4,8% alcohol ). Food and drinking water were ad libitum. The treatments were given daily for 30 days. The data were analyzed with anova. The result indicated that were not significant for all parameters. So, it was concluded that 0.04 mg diazepam, 100 ppm formalin and drink which contains 4,8% alcohol didn’t change the metabolism of M musculus body. Key words: diazepam, formalin and drink alcoholic